A real-time assay for neutrophil chemotaxis - Patricia M. Cano; Amandine Vargas; Jean-Pierre Lavoie (BioTechniques)
Neutrophils are the predominant cells during acute phases of inflammation, and it is now recognized that these leukocytes play an important role in modulation of the immune response. Directed migration of these cells to the sites of injury, known as chemotaxis, is driven by chemoattractants present at the endothelial cell surface or in the extracellular matrix (ECM). Since uncontrolled or excessive neutrophil chemotaxis is involved in pathological conditions such as atherosclerosis and severe asthma, studying the chemical cues triggering neutrophil migration is essential for understanding the biology of these cells and developing new anti-inflammatory therapies. Although several methods have been developed to evaluate neutrophil chemotaxis, these techniques are generally labor-intensive or alter the native form of these cells and their physiological response. Here we report a rapid, non-invasive, impedance-based, and label-free assay for real-time assessment of neutrophil chemotaxis.